Comparison of production costs and degree of pollution by emissions in the industrial sector of Ecuador using natural gas as fuel by means of process simulation - Peña Murillo, Sandra; López Diaz, Gabriel Junior (Ingeniería Química y Desarrollo, 2022)
In this investigation, the comparison of industrial costs and the degree of pollution due to emissions generated using traditional fuels, especially diesel, which is the most used in the Ecuadorian industry against natural gas through a program of Open source chemical engineering called DWSIM for the simulation of the chemical combustion reactions of diesel and natural gas as energy generators in the production processes of the Industries, in which it was evidenced that getting the same amount of energy can be obtained reduce up to 22.46% of carbon dioxide emissions to the environment using natural gas, a variation in production costs was also determined, which is a function of indirect manufacturing costs since in this element of costs Total production of fuels is found thus saving 3.9296% per month used natural gas as a fuel generator against diesel as traditional fuel
Keywords: Pollution; Carbon dioxide; Fuel; Natural gas